1988
DOI: 10.3109/00365548809032427
|View full text |Cite
|
Sign up to set email alerts
|

Beta-haemolytic Group A, B, C and G Streptococcal Septicaemia: A Clinical Study

Abstract: 87 beta-haemolytic streptococcal septicaemias in adult patients during 1979-86 in a university hospital were reviewed. 25% were caused by group A streptococcus, 17% by group B, 14% by group C and 44% by group G streptococcus. 67% of the septicaemias due to group B streptococcus were nosocomial, whereas the group A, C or G septicaemias were in most cases community-acquired. Alcoholism was the most common underlying disease in group A (32%) and malignancy in group G streptococcal septicaemias (45%). The most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
42
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 15 publications
13
42
3
Order By: Relevance
“…The epidemiology of group G beta-hemolytic streptococcal bacteremia in Hong Kong was found to be similar to that reported in previous studies (2,8,10,16,19). Most patients were old, with a predominance of males.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The epidemiology of group G beta-hemolytic streptococcal bacteremia in Hong Kong was found to be similar to that reported in previous studies (2,8,10,16,19). Most patients were old, with a predominance of males.…”
Section: Discussionsupporting
confidence: 82%
“…In one study, group G streptococci were shown to be the most common cause of beta-hemolytic streptococcal bacteremia (16). It has been reported that diabetes mellitus (DM), malignancy, cardiovascular disease, bone and joint diseases, and cirrhosis are the major underlying diseases in patients with group G beta-hemolytic streptococcal bacteremia (2,8,10,16,19). However, little is known about the relative importance of the various species and thus the source of bacteria causing bacteremia, the usefulness of commercial kits in identifying the species, and the factors that determine the outcome for patients with group G betahemolytic streptococcal bacteremia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, SDSE infections are very rare, encountered in the community at a rate of 0.003-0.006% and among hospitalized patients with a rate of 0.02-0.07% as the cause of acute non-gonococcal bacterial arthritis (2,5). Most patients with SDSE bacteremia are reported to be the elderly and males, with 74-100% rates having an underlying disease (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown in various studies that group G beta-hemolytic streptococci are the commonest cause of beta-hemolytic bacteremia in some parts of the world (12,16), relatively little is known about the other diseases caused by group G beta-hemolytic streptococci versus those caused by group A or group B beta-hemolytic streptococci. In our recent study, we showed that 52, 26, and 12% of patients with group G beta-hemolytic streptococcal bacteremia had primary bacteremia, cellulitis, and bed sore or wound infection, respectively, and that the remaining 10% had infective endocarditis, pneumonia, abscess, and septic arthritis (16).…”
mentioning
confidence: 99%